Animated Video Media on Clean and Healthy Living Behavior in Elementary School - Abu Qosim Almisfalah; Irma Yuliana (Universitas Pendidikan Ganesha, 2023)
There is a lack of learning resources that can inspire elementary school students to practice clean and healthy living. This study aims to produce an animation video media development product using software in the form of powtoon as a learning medium in elementary schools. The subjects in this study were students of grades II and III of elementary school, totaling 40 students. Data collection techniques in this study were observation, questionnaires, and interviews. Data analysis uses three stages, namely data reduction, data presentation, and drawing conclusions. Data validity uses sources and methods. In this study, teachers need learning media in the form of animated videos to raise students' awareness of Clean and Healthy Behavior, especially in the school environment. The results showed that 90% of students needed animated video media that had an attractive media appearance in the letters and language sections. Images that can support the explanation of the material, there is sound in the media when explaining the material, there are supporting animations when the Clean and Healthy Behavior material is delivered to get a percentage of 87.5% of students. 75% of students need media that has material coverage in accordance with basic competencies that are delivered widely but limited. 80% of students need media that can be accessed anywhere and anytime, teachers and students need media that contains examples and practice questions in animated video media.